The interleukin-6 gene –174G>C and –572G>C promoter polymorphisms are related to cerebral aneurysms. Issue 8 (28th April 2006) - Morgan, L; Cooper, J; Montgomery, H; Kitchen, N; Humphries, S E
Abstract : Background and aims: An important part is played by inflammation in intracranial aneurysm formation. The hypothesis that there is an association of the proinflammatory cytokine interleukin-6 (IL-6) genotypes (−572G>C and −174G>C) with intracranial aneurysms was tested. Methods: IL-6 genotypes were determined in 91 Caucasian patients with aneurysms and compared with 2720 healthy UK controls. Results: For both polymorphisms, the distribution of the genotypes and estimated allele frequency were different between the control group and the aneurysm group. For −572G>C, a higher frequency of the C allele (p = 0.001) and more people homozygous for the C allele were found among those with aneurysms than among the controls (4.4% v 0.3%, p = 0.001). For −174G>C, more people homozygous for the C allele were found among the controls than among those with aneurysm (18% v 7%, p = 0.007). The 572C/174G haplotype was associated with an increased risk of aneurysms, with the relative risk compared with the common haplotype being 1.89 and that for the −572G/174C haplotype being 0.58 (p<0.0005). Conclusion: This is the first study to show that IL-6 promoter polymorphisms are associated with intracranial aneurysmal disease. Whether this association is with the development, progression or rupture of such aneurysms, or represents survivor bias, is unclear.